Citizen science involving farmers as a means to document temporal trends in farmland biodiversity and relate them to agricultural practices. Issue 2 (23rd September 2020) - Billaud, Olivier; Vermeersch, Rose‐Line; Porcher, Emmanuelle
Abstract: Agricultural intensification is often recognized as a major driver of the decline of wild biodiversity in farmland. However, few studies have managed to collect relevant data to link the temporal dynamics of farmland biodiversity to the characteristics of intensive agriculture over large geographical areas. We used 7 years of data from a French citizen science programme, wherein 1, 216 farmers monitored biodiversity in 2, 382 fields encompassing field crops, meadows, vineyards or orchards, to examine the temporal trends in abundance of five taxonomic groups of invertebrates (solitary bees, earthworms, butterflies, beetles, molluscs) and their links with agronomic practices and surrounding landscape. We observed significant temporal trends in abundance for many taxonomic groups and in many crop types. Flying taxa (solitary bees and butterflies) were generally declining, while the trends of soil taxa were more variable. Most trends were significantly related to farming practices or landscape features. We observed a negative link between use of synthetic inputs (pesticides, mineral fertilization) and the trend in abundance of flying taxa in field crops, while in meadows organic or mineral fertilization was the main explanatory practice, with contrasting relationships across taxonomic groups. Besides, the trend in abundance of beetles and molluscs was more positive in permanent versus temporary meadows. Finally, in vineyards, the trend in abundance of solitary bees was positively related to the presence of woodland in the landscape, whereas the reverse was true in meadows. Synthesis and applications . Our results provide further support for the role of citizen science as a promising source of large‐scale spatial and temporal data in farmland, contributing to the identification of agronomic practices that can help mitigate biodiversity decline. Our analyses suggest that reducing chemical inputs may not only reduce the decline in bees and butterflies, but sometimes even promote their regrowth. Increasing organic fertilization may foster bee and beetle abundance in meadows but reduce mollusc abundance, while preventing ploughing of meadows may promote soil invertebrate abundance. Finally, such citizen science programmes engage farmers to undertake monitoring. Whether such group engagement may also contribute to biodiversity conservation by raising farmers' awareness remains to be addressed. Abstract : Our results provide further support for the role of citizen science as a promising source of large‐scale spatial and temporal data in farmland, contributing to the identification of agronomic practices that can help mitigate biodiversity decline. Our analyses suggest that reducing chemical inputs may not only reduce the decline in bees and butterflies, but sometimes even promote their regrowth. Increasing organic fertilization may foster bee and beetle abundance in meadows but reduce mollusc abundance, while preventing ploughing of meadows may promote soil invertebrate abundance. Finally, such citizen science programmes engage farmers to undertake monitoring. Whether such group engagement may also contribute to biodiversity conservation by raising farmers' awareness remains to be addressed. Résumé: L'intensification de l'agriculture est reconnue comme un facteur majeur du déclin de la biodiversité sauvage dans les terres agricoles. Cependant, peu d'études ont pu relier les changements temporels de la biodiversité agricole aux pratiques agricoles. Grâce aux données issues de l'Observatoire Agricole de la Biodiversité, un programme de science participative ayant rassemblé 1, 216 agriculteurs entre 2011 et 2017, pour un total de 2, 382 parcelles comprenant des grandes cultures, des prairies, des vignobles ou des vergers, nous avons étudié les tendances temporelles de l'abondance de cinq groupes d'invertébrés (abeilles solitaires, vers de terre, papillons, carabes, mollusques) et leurs liens avec les pratiques agronomiques et le paysage environnant. Nous avons observé des variations temporelles significatives de l'abondance pour plusieurs groupes taxonomiques et dans de nombreux types de cultures. Les taxons volants (abeilles solitaires et papillons) sont en général en déclin, tandis que les tendances des taxons terrestres sont plus variables. La plupart des tendances sont significativement corrélées aux pratiques agricoles ou au paysage. L'utilisation d'intrants de synthèse (pesticides et fertilisation minérale) est corrélée au déclin des taxons volants dans les grandes cultures, tandis que dans les prairies, la fertilisation organique et/ou minérale est la principale pratique explicative, avec des relations contrastées entre les groupes taxonomiques. En outre, les carabes et des mollusques sont en augmentation dans les prairies permanentes mais en déclin dans les prairies temporaires. Enfin, dans les vignobles, les variations d'abondance des abeilles solitaires sont positivement reliées à la présence de bois dans le paysage, alors que l'inverse est vrai dans les prairies. Synthèse et applications . Nos résultats confortent le rôle de la science citoyenne comme source prometteuse de données à grande échelle spatiale et temporelle dans les espaces agricoles, contribuant à l'identification des pratiques agronomiques qui peuvent aider à atténuer le déclin de la biodiversité. Nos analyses suggèrent que la réduction des intrants chimiques peut non seulement réduire le déclin des abeilles et des papillons, mais parfois même favoriser leur augmentation. Une fertilisation organique plus importante peut favoriser l'abondance des abeilles et des carabes dans les prairies mais réduire l'abondance des mollusques, tandis que le non‐retournement des prairies peut favoriser l'abondance des invertébrés du sol. Enfin, ces programmes de science citoyenne incitent les agriculteurs à observer la biodiversité de leurs parcelles. Reste à savoir si cet engagement collectif des agriculteurs peut également contribuer à la conservation de la biodiversité par une plus forte sensibilisation sur le sujet.